Association between total type I collagen N-terminal propeptide and coronary artery disease risk score in the general Japanese population. (August 2022) - Kikuchi, Hiroto; Nasu, Takahito; Satoh, Mamoru; Kotozaki, Yuka; Tanno, Kozo; Asahi, Koichi; Ohmomo, Hideki; Kobayashi, Takamasa; Taguchi, Satoru; Morino, Yoshihiro; Shimizu, Atsushi; Sobue, Kenji; et al.
Highlights: TP1NP levels decreased in participants with high CAD risk score and high baPWV. TP1NP downregulation may indicate future CAD risk and atherosclerosis progression. Abstract: Background: Bone metabolic dysregulation plays an important role in the pathogenesis of atherosclerosis; however, whether its markers contribute to coronary artery disease (CAD) risk in the general population remains unclear. Therefore, this study aimed to analyze the association between bone metabolic markers and CAD risk score in the general Japanese population. Methods: The Iwate Medical Megabank Organization collected individual participant data during a community-based cohort study in the Iwate prefecture (n = 5, 095, age = 58.9 ± 12.4 years). Participants with osteoporosis, chronic kidney disease, malignant disease, or primary wasting disease were excluded from the study. The present study measured the levels of circulating bone metabolic markers, including total type I collagen N-terminal propeptide (TP1NP), bone-type alkaline phosphatase, cross-linked N-telopeptide of type 1 collagen (NTX), and intact parathyroid hormone. CAD risk and atherosclerosis were evaluated using the Suita score and brachial–ankle pulse wave velocity (baPWV) measurement, respectively. Results: Among the bone metabolic markers, TP1NP was strongly associated with a high Suita score (≥56 points) (OR = 0.77, 95% CI = 0.69–0.82, P < 0.001). When participants were divided into quartiles of TP1NP levels, the subgroup with the lowest TP1NP level was associated with a high Suita score (≥56 points) and high baPWV (>1, 400 cm/s). Conclusions: This study demonstrated that TP1NP levels decreased in participants with high Suita scores and high baPWV, suggesting that TP1NP downregulation may indicate future CAD risk and atherosclerosis progression in the general Japanese population.